2020
DOI: 10.1039/d0ra00809e
|View full text |Cite
|
Sign up to set email alerts
|

Ni-mediated reactions in nanocrystalline diamond on Si substrates: the role of the oxide barrier

Abstract: Nanocrystalline diamond films grown on Si/native oxide substrates were subjected to Ni-mediated graphitization. Transmission electron microscopy study revealed crystals of NiSi2 and SiC across the carbon/silicon interface in addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In this case, the low temperature deposition process (at ∼ 330 • C) was used in order to avoid re-crystallization of metal layers at high temperatures, and minimize unwanted effects such as a catalytic graphitization of diamond [7], [8]. It is well-known, that the use of Ni on single-crystal and polycrystalline diamonds often results in the formation of graphitic layers at the Nidiamond interface or on top of the catalyst [9][10][11]. This effect is often utilized for the fabrication of graphene layers [10] or an array of sharp diamond microneedles [12].…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the low temperature deposition process (at ∼ 330 • C) was used in order to avoid re-crystallization of metal layers at high temperatures, and minimize unwanted effects such as a catalytic graphitization of diamond [7], [8]. It is well-known, that the use of Ni on single-crystal and polycrystalline diamonds often results in the formation of graphitic layers at the Nidiamond interface or on top of the catalyst [9][10][11]. This effect is often utilized for the fabrication of graphene layers [10] or an array of sharp diamond microneedles [12].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the underlying mechanisms of metal-catalyzed diamond etching have been revealed through HRTEM characterizations. 57,94,177 According to Tulic et al, graphite filled the channels along the diamond GBs during the nickel (Ni)-catalyzed etching process and a hemispherical Ni particle was present at the front of the graphite channels (Figure 6A). 94 The graphitic planes are covalently bonded to diamond with an upright orientation (Figure 6B).…”
Section: Metal-catalyzed Transitionmentioning
confidence: 99%
“…179 They also investigated the Ni-catalyzed phase transformation of thin NCD films formed on silicon wafers with native SiO 2 layer. 177 For the diamond synthesis process, the continuous SiO 2 layer remained at the relatively moderate plasma conditions, while the a-SiC can form from the SiO 2 at high-power plasma conditions. The permeability of SiO 2 and a-SiC layer to Ni can lead to different reactions.…”
Section: Metal-catalyzed Transitionmentioning
confidence: 99%
“…A superior interfacial bonding strength of ∼150 GPa was observed due to the formation of the covalently bonded diamond−graphene heterostructure. Tulićet al demonstrated the Ni-mediated graphitization of nanocrystalline diamonds on Si substrates by annealing in a tube furnace under vacuum condition at ∼1100 K. 253,254 The Ni particles catalytically etched the grain boundaries of diamond to release free carbon atoms, which covalently attached to the dangling bonds of diamond. As a result, the formed graphite planes were covalently bonded to the diamond surfaces in the perpendicular orientation (Figure 26a).…”
Section: Templated Synthesismentioning
confidence: 99%